Post-Traumatic Stress Disorder (PTSD) On a Sample Of The Brothers Of The Martyrs -Field Study In Area OF Jablah - - Sbeirah, Fouad; Sady, Reema; Badr , Eman (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to know existence of post traumatic disorder, and the differences in the degree of PTSD between males and females, as it aimed to detect the differences in the degree of PTSD depending on the variables; period of the shock , Educational level and social status. In This research it is used Davidson’s scale of PTSD ,which is based in the diagnosis DSM-IV which was translated to Arabic by Abdul Aziz Thabet (2006). The research is applied in Jableh. The sample consisted of (69) young (35) males and (34) females. The research is found the following results: there is post-traumatic stress disorder on a sample of the brothers of the martyrs in area OF Jablah, there is no statistically significant differences in the degree of PTSD between males and females, and Educational level , as too there are statistically significant differences in the degree of PTSD depending on the variables of a period of shock For a period of less than one year and social status research sample For the benefit of unmarried brothers .